2019
DOI: 10.1097/hnp.0000000000000351
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver-Delivered Foot Reflexology

Abstract: The aim of this study was to evaluate the effects of caregiver-delivered foot reflexology on patients with cancer and their caregivers. A 2-group pre- and posttest design was used in this study, and the study was conducted in an oncology hospital between January 2016 and February 2018. The study included 60 patients and 60 caregivers. Caregivers performed interventions once a day for 15 days. Patients in the experimental group received reflexology, and patients in the control group were included in the reading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
5
0
4
Order By: Relevance
“…However, study groups at baseline may have been imbalanced and there was no reporting of masking. 70,76 Overall, four studies demonstrated at least small benefits of foot reflexology with short-term interventions. No study reported significant adverse events.…”
Section: Recommendationsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, study groups at baseline may have been imbalanced and there was no reporting of masking. 70,76 Overall, four studies demonstrated at least small benefits of foot reflexology with short-term interventions. No study reported significant adverse events.…”
Section: Recommendationsmentioning
confidence: 99%
“…141 Thus, the benefits of yoga for people with metastatic cancer and intervention duration in people with localized or regionally advanced cancer requires further study. Hypnosis RCT 9 Anxiety [39][40][41][42][43][44][45] Anxiety and depression 46,47 Mindfulness-based interventions SR 7 Anxiety and depression [48][49][50][51][52][53][54] RCT 7 Depression 55,56 Anxiety and depression [57][58][59][60][61] Music therapy and music-based interventions SR 4 Anxiety and depression [62][63][64][65] RCT 4 Anxiety [66][67][68] Reflexology RCT 9 Anxiety [69][70][71][72] Anxiety and depression [73][74][75][76][77] Relaxation techniques SR 4 Anxiety and depression [78][79][80][81] RCT 5 Anxiety and depression [82][83]…”
Section: Recommendationsmentioning
confidence: 99%
See 3 more Smart Citations